The Effect of the ICARE Learning Model in Distance Learning on the Mathematical Problem Solving Ability of SMK Negeri 2 Karawang Students - Al Wanita Imani Hikmatuprilla; Lukita Ambarwati; Dwi Antari Wijayanti (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2021)
This study aims to obtain empirical information about the effect of implementing the ICARE learning model (Introduction, Connect, Apply, Reflect, Extend) in distance learning on students’ problem-solving abilities at SMK Negeri 2 Karawang. The research method used was a quasi-experimental with posttest-only control group design. The population in this study were all class X students at SMK Negeri 2 Karawang. Sampling using Cluster Random Sampling to determine the affordable population and Simple Random Sampling to determine the sample. Class X TB 1 was chosen to be the experimental class and class X TB 3 was selected as the control class. The results of the statistical hypothesis testing were then carried out using the the-test of two independent samples with a significant level of 5% concluded that the mean test results of students' mathematical problem-solving abilities in the experimental class were higher than the control class. The large effect test carried out obtained the result of d = 0.8, this shows that the ICARE learning model in distance learning has a significant effect on the mathematical problem-solving abilities of students at SMK Negeri 2 Karawang on the sequence and series material. The influence given is 79% and is included in the large category. Keywords: Learning Model ICARE (Introduction, Connect, Apply, Reflect, Extend), Distance Learning, Mathematical Problem Solving Ability